High performance chrome free coating for white rust protection of zinc. Issue 1 (January 2016) - Bera, S.; Udayabhanu, G.; Narayan, R.; Rout, T. K.
Abstract : Development of chrome free coatings for white rust (corrosion) protection of galvanised steel is a key concern for scientists worldwide. The present work presents the results of an investigation on the effect of amine and thiol functional groups bearing silane coupling agents such as 3-phenyl-aminopropyl-triethoxy silane and mercapto-propyl-tri methoxysilane respectively on anticorrosion properties of a reference sol–gel solution. Anticorrosion performance of the coatings was evaluated by potentiodynamic polarisation method and AC impedance spectroscopy. Accelerated corrosion test was performed using salt spray chamber and compared with a chromate coated galvanised sheet. The results clearly revealed that the addition of silane containing thiol group to the reference coating solution produced remarkable improvement in hydrophobicity and corrosion resistance compared to amine group.